Sous l'empire du royaume: poét(h)ique de la fiction coloniale issue du Congo belge (1945-60) - Fraiture, Pierre-Philippe (2002)
This thesis intends to explore colonial fictions written in French and set in the former Belgian Congo between 1945 and 1960. The investigation will focus on George Duncan (1898-1967), Henri Cornélus (1913-1983), Marcel Tinel (1904-?) and Joseph Esser (1901-?). The thesis - throughout - will endeavour to focus on both ethics and poetics. In order to achieve this overarching (double) objective it will attempt to address the following questions: (1) how are colonised subjects and colonisers represented by this fictional material? (2) how do colonial novelists account for and/or sympathise with the emergence of a Congolese opposition after the Second World War? (3) what are the implicit and explicit strategies deployed by the corpus to support or question the discourse(s) on which Belgian colonialism was premised? (4) what is colonial imagination? Did it decolonise itself - and if so how? - with the demise of the Belgian empire in 1960? In its poet(h)ical investigation this thesis will rely (a) on a range of representatives of postcolonial thinking such as Sartre, Fanon, Mouralis, Glissant and Mudimbe, (b) as well as a number of literary critics whose work is of relevance for my study. Chapter I will contextualise the thesis from both a critical and an historical standpoint and fall into four distinct parts. Part i will provide a historical overview of the Congo under Belgian rule. Part ii will concentrate on Belgian colonial discourse with a particular emphasis on its main ideologue, Pierre Ryckmans (1891-1959). Part iii will deal with the two colonial art and literary critics Gaston-Denys Périer (1879-1963) and Joseph-Marie Jadot (1886-1967) and their attempt to (a) promote colonial writing and (b) create synergies between 'white' and 'black' literatures at a time (1945-60) which coincided with the emergence of the first Congolese writers in French under the auspices of the journal La Voix du Congolais. Part iv will focus on the reassessment of Belgian colonial literature by contemporary critics. Chapters II to V will be author-based. In each case a central text will be read with / against a number of other primary sources. Chapter II will deal with Duncan's five colonial novels and their recurring main protagonist with a particular emphasis on Blancs et Noirs (1949). Chapter III will read Cornélus' novel Kufa (1954) against his collection of short stories Bakonji. Les Chefs, (1955). Whereas Duncan's and Cornélus' fictions primarily concentrate on white male subjects for whom Central Africa is a mere theatrical backdrop meant to be metaphorically mirroring the decline of Western civilisation, Tinel and Esser give their preferences to Congolese protagonists and engage more deeply with local cultures. Chapter IV will attempt to interpret Tinel's novel Le Monde de Nzakomba (1959) in the light of (a) Tinet's journalistic pieces on the colonial situation and (b) with regard to 'négritude', one of the underlying themes of the novel. In Chapter V the reading will focus on Esser's novel Matuli, fille d'Afrique (1960). As for Tinel, the interpretation will also rely on Esser's non fictional writing, the bulk of which is dealing with bantou culture. The conclusion of the thesis will propose a paradigmatic categorisation of the Belgian colonial corpus during the given period.